2021
DOI: 10.1186/s12912-021-00764-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated familiarity with autism spectrum disorders among practicing nurses: a cross-sectional study in the palestinian nursing practice

Abstract: Background Autism spectrum disorders (ASDs) are one of the most prevalent neurodevelopmental disabilities of early childhood. Practicing nurses are in a key position to help patients with ASDs and/or their caregivers/families. This study was conducted to assess self-rated familiarity with ASDs among practicing nurses in Palestine. The study also aimed to identify the sociodemographic and practice variables that could predict high self-rated familiarity scores. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Moreover, in our study, 40.2% of the participants reported diagnosing and treating patients with autism, which is higher in comparison to a previous study, done by Altay M, which was conducted among family medicine physicians and reported that 70.8% of the participants had seen autism cases [25] . Per studies that medical students and different medical staff [26,27] , approximately 80.8% of participants in the current study were aware that children with ASDs had deficits in social interaction, communication or language, and behavioral development. However, a concerning finding was that only approximately 61.9% of participants correctly recognized the higher susceptibility of males to Autism Spectrum Disorders (ASDs), aligning with a study conducted in Palestine by Shawahna et al [28].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, in our study, 40.2% of the participants reported diagnosing and treating patients with autism, which is higher in comparison to a previous study, done by Altay M, which was conducted among family medicine physicians and reported that 70.8% of the participants had seen autism cases [25] . Per studies that medical students and different medical staff [26,27] , approximately 80.8% of participants in the current study were aware that children with ASDs had deficits in social interaction, communication or language, and behavioral development. However, a concerning finding was that only approximately 61.9% of participants correctly recognized the higher susceptibility of males to Autism Spectrum Disorders (ASDs), aligning with a study conducted in Palestine by Shawahna et al [28].…”
Section: Discussionmentioning
confidence: 92%
“…This is one of the few studies of an MCHN population that examines key competencies influencing ability to identify and support families with an infant or toddler at a high likelihood for autism, and the predictors of these capabilities. Little known previous research has examined relationships with, and predictors of, confidence in speaking with parents/caregivers about autism in a healthcare professional population, with previous studies only measuring this as an outcome of training in most instances, with the exception of Shawahna and colleagues ( 41 ). Other strengths include the large sample size in the TNS, which increases confidence in generalizability of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of healthcare professionals’ confidence appear to have been considered when evaluating autism training effectiveness ( 30 , 31 ). However, a 2021 study of 357 practicing nurses in Palestine found that only 9% of nurses felt confident counseling parents about autism ( 41 ). A moderate positive correlation was found between autism knowledge and confidence in discussing autism with parents, as well as a significant relationship between years of practice and continuing education on autism and increased knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Tis suggests that more comprehensive training programs are necessary for health professionals to not only improve their knowledge of ASD but also ensure the provision of appropriate care for individuals with ASD. Research has shown that specialized training in ASD has been associated with signifcantly higher knowledge scores among nurses compared to those without such training [34]. Tis highlights the importance of continuing education and training for healthcare professionals [34].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that specialized training in ASD has been associated with signifcantly higher knowledge scores among nurses compared to those without such training [34]. Tis highlights the importance of continuing education and training for healthcare professionals [34]. Yet, misconceptions and stigmatizing attitudes towards individuals with ASD still exist in the Gulf state of Saudi Arabia [20].…”
Section: Discussionmentioning
confidence: 99%